Sampah Keliling (SALING): Edukasi dan Pemberdayaan Masyarakat Desa Sungai Bangkal, Banjar, Kalimantan Selatan - Iskandar, Iskandar; Praditya, Angga; Prastricia, Meily Andini; Yaliza, Nella; Suhartono, Eko (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2025)
Knowledge and attitudes of community groups are important aspects of fostering awareness and good behaviour regarding waste management.  This increase in knowledge and attitudes can be enhanced through health promotion activities.  Based on this, the community service activity called the SALING program (Mobile Waste) was carried out with the aim of improving the attitude, knowledge, behaviour, and participation of the Sugai Bangkal Village community towards waste management.  This activity consists of three stages: preparation, implementation, and evaluation.  The preparation stage is carried out through coordination with the Pembakal/Head of the Village regarding the implementation of the program, timing, and location.  Next, the implementation of the activities consists of delivering education and forming cadres and a waste management system.  The results of this activity have proven to increase the community's knowledge, attitudes, and awareness regarding waste management.  This is based on the evaluation results through pre- and post-tests conducted before and after the implementation.  In conclusion, the SALING community service activities have proven effective in improving the community's attitudes, knowledge, and awareness regarding the importance of a good waste management system.